2020
DOI: 10.1016/j.pec.2020.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Open dialogue about complementary and alternative medicine (CAM) integrated in conventional oncology care, characteristics and impact. A systematic review

Abstract: OBJECTIVE: To systematically review evidence on the characteristics, experiences and impact of an open dialogue about complementary and alternative medicine (CAM) integrated in oncology care. METHODS: We searched MEDLINE, EMBASE, AMED, Scopus, ProQuest Dissertations and Thesis, Cochrane Central Register, clinicaltrials.gov, forskningsdatabase.dk and PROSPERO. Two reviewers screened title, abstract and full-text articles. Each study was appraised using the Critical Appraisal Skills Programme (CASP) and synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…It will also add to the evidence-based knowledge on communication about CAM between patients and health professionals in clinical practice. Only few studies have exclusively explored the effects OD-CAM integrated in conventional oncology care 26. Most of them include both open dialogue and the provision of CAM and mainly assess patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It will also add to the evidence-based knowledge on communication about CAM between patients and health professionals in clinical practice. Only few studies have exclusively explored the effects OD-CAM integrated in conventional oncology care 26. Most of them include both open dialogue and the provision of CAM and mainly assess patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…The fundamental starting point of integrative oncology is that patients and health professionals openly discuss safe and healthy use of CAM 9. Studies have shown that counselling about CAM as an integral part of conventional oncology treatment engages patients in their own healthcare, increases patient-centred communication and leads to higher clinician25 and patient satisfaction 26. Counselling about CAM also addresses patient stress and uncertainty because it reduces exposure to misleading information.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, considering the high rate of CAM use among Danish cancer patients [ 5 ], there is a need for health professionals and patients to have an open dialogue about the potential benefits and harms of CAM when combined with conventional oncology treatment [ 27 , 28 ]. Studies have shown that open dialogue about CAM increases patient engagement, patient-centered communication and higher clinician [ 29 ] and patient satisfaction [ 30 ]. It addresses patient stress and uncertainty, reduces exposure to misleading information and enhances the patient–physician relationship, which is paramount in delivering high-quality care [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, with the increased use of medication comes the risk of more adverse effects and opioid dependency (Bosetti et al, 2019;Tick et al, 2018). More and more, both health care professionals and patients call for de-medicalization and show greater interest in the complementary use of non-pharmacological interventions (NPIs) (Breivik et al, 2013;Fjaer et al, 2020;Greenlee et al, 2017;Hall et al, 2018;Qaseem et al, 2017;Rogge et al, 2021;Stie et al, 2020).…”
Section: Introductionmentioning
confidence: 99%